Wood Nutrient-Water-Density Linkages Are Influenced by Both Species and Environment - Lira-Martins, Demetrius; Quesada, Carlos Alberto; Strekopytov, Stanislav; Humphreys-Williams, Emma; Herault, Bruno; Lloyd, Jon (Frontiers in Plant Science, 2022)
Tropical trees store a large amount of nutrients in their woody tissues; however, the physiological role of these elements remains to be identified. Given the osmotic activity of mineral elements such as potassium, sodium and calcium, these elements should be strong candidates in mediating water storing capacity in tropical trees. We investigated the role of wood nutrients in facilitating wood water storage in trees by using branch samples from 48 tropical tree species in South America and examined their associations with wood density (ρ). We found that lower wood density trees store more water in their woody tissues with cations, especially potassium, having a positive association with water storage. Specific relationships between wood cation concentrations and stem water storage potential nevertheless depend on both species’ identity and growing location. Tropical trees with increased water storage capacity show lower wood density and have an increased reliance on cations to regulate this reservoir. Our study highlights that cations play a more important role in tropical tree water relations than has previously been thought, with potassium being particularly important.